Structure-Activity Relationships of Dopamine Transporter Pharmacological Chaperones - Sutton, Charles; Williams, Erin Q.; Homsi, Hoomam; Beerepoot, Pieter; Nazari, Reza; Han, Dong; Ramsey, Amy J.; Mash, Deborah C.; Olson, David E.; Blough, Bruce; Salahpour, Ali (Frontiers in Cellular Neuroscience, 2022)
Mutations in the dopamine transporter gene (SLC6A3) have been implicated in many human diseases. Among these is the infantile parkinsonism-dystonia known as Dopamine Transporter Deficiency Syndrome (DTDS). Afflicted individuals have minimal to no functional dopamine transporter protein. This is primarily due to retention of misfolded disease-causing dopamine transporter variants. This results in a variety of severe motor symptoms in patients and the disease ultimately leads to death in adolescence or young adulthood. Though no treatment is currently available, pharmacological chaperones targeting the dopamine transporter have been shown to rescue select DTDS disease-causing variants. Previous work has identified two DAT pharmacological chaperones with moderate potency and efficacy: bupropion and ibogaine. In this study, we carried out structure-activity relationships (SARs) for bupropion and ibogaine with the goal of identifying the chemical features required for pharmacological chaperone activity. Our results show that the isoquinuclidine substituent of ibogaine and its analogues is an important feature for pharmacological chaperone efficacy. For bupropion, the secondary amine group is essential for pharmacological chaperone activity. Lastly, we describe additional ibogaine and bupropion analogues with varying chemical modifications and variable pharmacological chaperone efficacies at the dopamine transporter. Our results contribute to the design and refinement of future dopamine transporter pharmacological chaperones with improved efficacies and potencies.